Perception of misinformation on social media among Chinese college students - Jiang, Bowen; Wang, Desheng (Frontiers in Psychology, 2024)
Background: Chinese college students predominantly use social media applications to collect information, communicate with each other, advance their education, and go shopping. Research has highlighted the spread of misinformation or fake news on social media, and this has affected college students negatively as they are the most frequent users of social media. Objective: This research aims to investigate Chinese college students’ perceptions of misinformation on social media, including their views on the consequences of misinformation, insights into the reasons for its dissemination, how misinformation impacts their mental health, and their perspectives on how to control misinformation. Methods: This study followed a qualitative approach, selecting 36 participants from 12 universities in China, collecting data through semi-structured interviews, and analyzing the data to enable thematic analysis. Results: Chinese college students are aware of the adverse impact of spreading misinformation on social media. They believe that false information is disseminated primarily due to inadequate punishment for those who intentionally spread it. Most college students lack proficiency in identifying misinformation, and they expect the government to do more to control the misinformation phenomenon. Moreover, misinformation on social media may cause Chinese college students to feel dysphoric, angry, and even depressed, thereby affecting their mental health. This research indicates that the public and government should make efforts to address the misinformation phenomenon in order to protect college students from being harmed.